Strategic Entrepreneur ship and its role in a marketing performance - Mohamed, Ali Ahmed; Alhamd, Alaa Dham (Journal of Economics and Administrative Sciences, 2020)
The current research aims through its chapters to verify the relationship and impact of strategic leadership as an independent variable in the marketing performance as a respondent variable, in a leap cement plant, and try to come up with a set of recommendations that contribute to enhancing the practice and adoption of the two variables in the organization under discussion. And based on the importance of the research topic to the community, and to the researched organization and its members, the analytical and analytical approach was adopted in the completion of this research, and the research community included a leap cement plant in Anbar Governorate, while the research sample was represented by (department heads, and people officials) as a class intentional sample, when the researcher distributed (80) Questionnaire of the research sample, then collected data from (75) respondents, excluding them (3), so it became good for them to analyze (72) from the research community by adopting the questionnaire that included (46) paragraphs, and providing them with personal interviews as aids in strengthening them. The research adopted the program (Amos V.25, SPSS V.25) with the adoption of methods of descriptive and inferential statistics (natural distribution test, confirmatory factor analysis, arithmetic mean, percentages, standard deviation, relativistic importance, difference coefficient, correlation coefficient Pearson, the simple regression coefficient,) to test his hypotheses. As for the most prominent results of the research, the possession of a leap cement factory led to a marketing performance that strengthens it through strategic leadership, especially when it is interested in employing the entrepreneurial mindset and owning strategically managed resources and promoting culture and entrepreneurial leadership. His pioneering strategies in that promotion.